ANALYSIS OF FINANCIAL MANAGEMENT BEHAVIOR STUDENTS OF THE FACULTY OF ECONOMICS SEMARANG UNIVERSITY IN A PANDEMIC PERIOD WITH SELF-CONTROL AS A MEDIATION VARIABLE - Bonita Prabasari; Windasari Rachmawati; Ahmad Sahri Romadon (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This purpose of this research is to know whether there is influence of gender to financial management behavior either directly or through self control as mediation variable. This study uses a quantitative approach. Data collection in this study used primary data by distributing questionnaires to students of the economics faculty of the University of Semarang by spreading the google form link through the whatsapp application to student. The technique used in sampling is purposive sampling. The number of questionnaires that were processed were 100 questionnaires. Data were analyzed using path analysis and sobel test. The result of this study indicate (1) there is not influence of gender to financial management behavior (2) there is influence of self control to financial management behavior (3) there is influence of gender to self control (4) there is of gender to financial management behavior through self control.